Improvement in the quality of life of patients with persistent or long-standing persistent atrial fibrillation after hybrid ablation - Osmancik, Pavel; Budera, Petr; Talavera, David; Herman, Dalibor; Vesela, Jana; Prochazkova, Radka; Rizov, Vitalii; Kacer, Petr (Journal of interventional cardiac electrophysiology, 2020)
BACKGROUND: Hybrid ablation (i.e., a combination of a thoracoscopic surgical ablation followed by a catheter ablation) is a treatment option for patients with non-paroxysmal atrial fibrillation (AF). Despite its promising efficacy, it is a surgical procedure with a relatively high risk of complications that could affect the quality of life (QoL) of patients, even when sinus rhythm is restored. OBJECTIVE: To describe changes in the QoL of patients with non-paroxysmal AF before and after a hybrid ablation. METHODS: Patients after hybrid ablation for persistent or long-standing persistent AF were prospectively studied. Follow-up visits were scheduled at 1, 3, 6, 9, and 12 months. The maintenance of SR was assessed using 1-week Holter recordings at 6 and 12 months and 24-h Holter recordings at 3 and 9 months, or via an implantable loop recorder. QoL was assessed using the Atrial Fibrillation Effect on Quality-of-life (AFEQT) and the EuroQoL-5Dimensions (EQ-5D) questionnaires before and 12 months after ablation. RESULTS: Seventy-five patients (49 men, age 62.9 ± 8.45 years, 48 (64%) with long-standing persistent AF) were enrolled. Fifty-two (69.3%, SR group) were AF-free during the 12-month follow-up, 16 (21.3%, PAROX group) had only paroxysms of AF after ablation, and 7 (9.3%, PERM group) were on rate control due to permanent AF reoccurrence. The AFEQT score increased significantly in the SR group from 59.9 ± 19.4 to 91.4 ± 10.8 (p < 0.001), and in the PAROX group from 58.8 ± 19.0 to 81.5 ± 14.1 (p = 0.002) but remained unchanged in the PERM group (44.6 ± 7.5 vs. 47.4 ± 5.5, p = 0.24). The EQ-5D score significantly decreased in the descriptive part (from 7.90 ± 2.61 to 6.64 ± 1.90, p = 0.0001) and increased on the visual analog scale (from 63.56 ± 19.11 to 79.30 ± 16.9, p < 0.0001) in the SR group. In the PAROX group, no significant change was present on either the descriptive part (p = 0.3) or in the visual analog scale (p = 0.48). Similarly, no significant changes were present on either the descriptive part (p = 0.93) or the visual analog scale (p = 0.4) in the PERM group. CONCLUSION: The QoL of patients with non-paroxysmal AF and patients with AF paroxysms, after successful hybrid ablation, improved significantly in patients with SR. No significant improvement was present in patients on rate control after an unsuccessful ablation.
Keywords: průzkumy a dotazníky; Female; elektrokardiografie ambulantní; Atrial Fibrillation; Quality of Life; ženské pohlaví; Surveys and Questionnaires; Catheter Ablation; kvalita života; lidé; katetrizační ablace; prospektivní studie; Male; Prospective Studies; Electrocardiography, Ambulatory; fibrilace síní; lidé středního věku; mužské pohlaví; torakoskopie; Middle Aged; Thoracoscopy; Humans